Practical problems before privacy concerns: How European energy community initiatives struggle with data collection. (April 2023) - Heuninckx, Shary; Meitern, Maarja; te Boveldt, Geert; Coosemans, Thierry
Abstract: Energy communities (ECs) are increasingly put forward as one of the solutions for making the European energy system greener and more resilient, through the local production and sharing of renewable energy. In order to design and operate an efficient EC, data on energy consumption and production is needed. This allows to determine the optimal market model and the necessary investments needed for renewable assets. Unfortunately, the acquisition of energy data is often the biggest barrier for EC initiators. This paper brings together the various hurdles in data acquisition that were identified through interviews with 10 EC initiators throughout Europe. Contrary to the existing literature we found that consumers seem less hesitant to share their data than suggested, as many show little concern for data protection. The major hurdles identified are related to the physical assets, such as data gathering and smart meter installation procedures taking more effort and time than planned, as well as to the low quality of existing data. Our research shows that many EC initiators face similar but rarely mentioned hurdles, that could be mitigated and overcome easier when considered beforehand.